Overview of The Characteristics of Online Gambling Among Adolescents in Kajar Village - Sri Hindriyastuti; Silfia Istikomah; Gardha Rias Arsy; Wahyu Yusianto (Lembaga Pengembangan Kinerja Dosen, 2023)
Online gambling has the meaning of gambling that can be done through online platforms such as sites or online game applications that have the smell of gambling. With the convenience due to technological developments, it has also become easier for people to do online gambling. Online gambling as one of the negative technological developments in the electronics sector needs to be addressed from various angles because the impact is returned to its users, especially teenagers. The characteristics of adolescents who gamble online vary, so the purpose of this study is to describe the characteristics of adolescents who gamble online. The type of research used is quantitative research with a descriptive approach. The data collection used is to distribute a checklist of observations related to the description of the characteristics of online gambling. The results of the study of 30 respondents to the Characteristics of Online Gambling in Adolescents showed that the respondents who did online gambling on average graduated from high school as many as 18 respondents (60%), were male (93.3%), with an age range of at most 20 -22 years (66.7%), the type of gambling played is higgs domino (73.3%), and gambling using capital from their own work (93.3%). Many teenagers consider online gambling behavior normal.